Metode Pendidikan Islam di dalam Q.S. Al-Baqarah Ayat 258-259 - Zubaidah (IAI DARUL ULUM KANDANGAN, 2023)
Q.S. Al-Baqarah verses 258-259 perpetuate two stories of the past that store ibrah in them, not to mention that these two verses describe several methods of Islamic education that can be applied in the learning process. These two verses tell about the debate between Prophet Ibrahim and King Namrud, then tells the story of the story of Uzair's sleeping for 100 years. As for the formulation of the problem in this study, what are the methods of Islamic education from the perspective of Q.S. Al-Baqarah verses 258-259. This type of research is library research. The subject as well as the object is Q.S. Al-Baqarah verses 258-259 along with the methods of Islamic education contained therein. The data was collected by using library survey techniques, documentation, and processed by editing, interpreting and classifying data, then the data was analyzed using the content analysis method. From the results of the study, it was concluded that the Islamic education method contained in Q.S. Al-Baqarah verses 258-259 are (1) story/story method (2) lecture method (3) punishment (targhib) method (4) dialogical method/question and answer (5) demonstration method (6) assignment method (7) group work method.